KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN KLEGO KABUPATEN BOYOLALI - Joko Suranto, Anindhyta Angga TMTP, Qomarudin & (Transformasi, 2016)
The purpose of this research is to analize the quality of public service in Klego subdistrict officein Boyolali regency. This research uses descriptive method with qualitative approach. Theresearch informant use purposive sampling technique. The technique of data collection useobservation, interview and documentation. The data analysis technique use interactive analysiswhich consist of data reduction, data presentation, and conclution. The result of this researchshows the quality of the service of Klego subdistrict based on the fact dimention which is not tosatisfy enough for the people. The unsatisfied service are such as the less of queue seat and theemployee discipline factor. There are some employee still have in discipline the employee isgood enough in giving the service to the public, but there is still any some capability that shouldbe better, such as the ability in operating the computer program. If we see from capacity of theperceptive, it is not show the good quality of service. It seen when responding the requester, notevery requester get the good response from the employee. There are some employee have theability to give thee good respons to the requester. The good respons mostly showed fot therequester who have the colleague or the requester who have a good relation with the emloyee.The ansurance dimention shows the good service, it gives the good service to the people and itgives legality and it olso free that the service which was did by the employee of that districtalways give the legality asurance for the people. If we see from the empathy dimension it showsthe good quality when did there duty, the employee put the importance of the requester in thefirst place.Keywords: tangibles, reliability, responsiveness, assurance and empathy.